2019
DOI: 10.21203/rs.2.213/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of a heel-unloading orthosis in short-term treatment of calcaneus fractures on physical function, quality of life and return to work – study protocol for a randomized controlled trial

Abstract: Background Neither for operative nor non-operative therapy standardized guidelines for rehabilitation of calcaneus fractures are existing. While there is consensus for non- or partial weight bearing, the use of supporting devices such as specific foot ankle orthosis is still a matter of debate. Recently, a heel-unloading orthosis (‘Settner shoe’) was introduced for aftercare of these fractures, allowing walking by shifting the load to the middle- and forefoot. This orthosis enables early mobilization of patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, only one other study has compared matched patient backgrounds. 12 The most important finding of our study is that the AOFAS score was significantly better in group O than in group C at 3 months after surgery. In terms of the AOFAS components, pain and walking distance scores at 3 months after surgery were predominantly higher in group O, which means that pain was significantly lower and maximum walking distance longer at 3 months after surgery in group O.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…To the best of our knowledge, only one other study has compared matched patient backgrounds. 12 The most important finding of our study is that the AOFAS score was significantly better in group O than in group C at 3 months after surgery. In terms of the AOFAS components, pain and walking distance scores at 3 months after surgery were predominantly higher in group O, which means that pain was significantly lower and maximum walking distance longer at 3 months after surgery in group O.…”
Section: Discussionsupporting
confidence: 49%
“…8 Heel-unloading orthoses (HUOs) including the Settner shoe, Mars shoe, M ünchen shoe, and Graffin orthosis in Japan (Figure 1) make patients with calcaneus fractures walk after surgery by shifting the load to the forefoot and midfoot and achieve early mobilization. [9][10][11][12] A prior study also reported that the heelunloading brace for calcaneal fracture improved the range of motion (ROM) of the ankle joint. 13 However, few studies have validated the efficacy and biomechanics of the Graffin orthosis after surgery.…”
Section: Introductionmentioning
confidence: 99%